2016
DOI: 10.4178/epih.e2016043
|View full text |Cite
|
Sign up to set email alerts
|

Levels of adherence and factors associated with adherence to option B+ prevention of mother-to-child transmission among pregnant and lactating mothers in selected government health facilities of South Wollo Zone, Amhara Region, northeast Ethiopia, 2016

Abstract: OBJECTIVESThe aim of this study was to measure the levels of adherence and to identify factors associated with adherence to option B+ prevention of mother-to-child transmission (PMTCT) among pregnant and lactating mothers in selected government health facilities of South Wollo Zone, Amhara Region, northeast Ethiopia.METHODSAn institution-based cross-sectional quantitative study design was employed from March 1, 2016 to April 14, 2016, using a standard structured data collection instrument. A sample of 191 huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 11 publications
4
27
1
Order By: Relevance
“…In Ethiopia, report that immunological treatment failure is associated with old age. 18 Furthermore, in North-West Ethiopia, each unit increase in years is associated with a 3.3% cell/mm 3 decrease in the log of change of CD4 cell count (0.0098, 0.0899); p=0.0264. 13 Patients with lower CD4 cell count at ART initiation and more advanced age (> 40 vs <40 years) demonstrate a decline in CD4 cell count from baseline to 12, 24, and 36 months of follow-up.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In Ethiopia, report that immunological treatment failure is associated with old age. 18 Furthermore, in North-West Ethiopia, each unit increase in years is associated with a 3.3% cell/mm 3 decrease in the log of change of CD4 cell count (0.0098, 0.0899); p=0.0264. 13 Patients with lower CD4 cell count at ART initiation and more advanced age (> 40 vs <40 years) demonstrate a decline in CD4 cell count from baseline to 12, 24, and 36 months of follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…On the contrary, it is suggested that immunological treatment failure is associated with lower baseline CD4 count and higher educational status. 18 According to the study conducted in Addis Ababa, it is showed that women with lower CD4 count before ART initiation<200 cells/mm 3 are 0.023 times less likely to achieve good immunological outcome compared to those with CD4 count ≥200 cells/mm 3 (AOR=0.023, 95% CI= (0.003-0.190), p=0.000) among women who start HAART before or during pregnancy in a Hospital in Addis Ababa. 20…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study were similar with other studies. [28][29][30] In our study findings delivered at home were the main determinant factors for vertical transmission of HIV to their infants. During the follow-up, 73 (35.96%) infants were delivered at home; among those mothers, 16 (21.9%) infants were HIV positive that delivered at health institutions.…”
mentioning
confidence: 44%
“…Various PMTCT programmes use different methods for measuring adherence. However, common measures include self and proxy reports, pill counts, pharmacy refills, electronic drug monitoring, virologic markers (CD4 counts, viral loads) and blood draws for drug concentrations.On the other hand report a higher proportion of 87.1% (95% CI 82.6-90.7%) among HIV-positive pregnant women on option B+ with adequate adherence in Tigray, northern Ethiopia reports a similar percentage of 95.9% (306) among women on option B+ with good adherence compared to 12.1% (n=23) with poor adherence in Amhara region, North East Ethiopia (17). A much higher proportion of pregnant and breastfeeding women on option B+ (91.4%) have good adherence to ART (≥95% adherence) (MSPH 2015:10).…”
Section: Discussionmentioning
confidence: 93%